2018
DOI: 10.1007/s12105-018-0985-4
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of Cancer Stem Cells Marker ALDH1 and its Association with Tumor Budding in Oral Squamous Cell Carcinoma

Abstract: Tumor budding is a prognostic marker for oral squamous cell carcinoma (OSCC) characterized by the presence of isolated or small clusters of neoplastic cells at the tumor invasive front. Aldehyde dehydrogenase-1 (ALDH1) is associated with tumorigenesis, linked to treatment resistance and shown to identify cancer stem cells (CSC)-like cells. This study aimed to evaluate the expression of ALDH1 and its association with tumor budding in OSCC. Immunohistochemistry was employed in 163 OSCC samples to identify pancyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 36 publications
2
22
0
3
Order By: Relevance
“…Moreover, high ALDH1 expression was recently associated with a high intensity of tumor budding. This reinforces the role of CSCs in carcinogenesis through ALDH1 expression, which can accelerate the invasion of cancer cells and, consequently, worsen the biological tumor behavior ( 28 ).…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, high ALDH1 expression was recently associated with a high intensity of tumor budding. This reinforces the role of CSCs in carcinogenesis through ALDH1 expression, which can accelerate the invasion of cancer cells and, consequently, worsen the biological tumor behavior ( 28 ).…”
Section: Discussionsupporting
confidence: 63%
“…This is followed by migration of cancer cells away from the main tumor body toward deeper parts of the affected organ and in some instances by various routes toward distant organs (ie, metastasis). In oral squamous cell carcinoma (OSCC), a recent study by Marangon Junior et al 13 in tumors having a high density of budding, the expression of ALDH1 was higher in the area of buds than in areas outside tumor budding. In a three-dimensional assessment of tumor budding, 6 however, cancer cell invasion was reported as a collective migration of cells, and migration of single cancer cells was deemed rare.…”
Section: Tumor Budding Invasion and Metastasismentioning
confidence: 98%
“…In nasopharyngeal carcinoma, Luo et al 9 reported that tumor budding cells had a high expression of the cancer stem cell marker, aldehyde dehydrogenase 1 (ALDH1), and proposed that budding cells might have the invasive and metastatic characteristics of the cancer stem cells. In oral squamous cell carcinoma (OSCC), a recent study by Marangon Junior et al 13 in tumors having a high density of budding, the expression of ALDH1 was higher in the area of buds than in areas outside tumor budding. They explained this pattern of ALDH1 expression as a consequence of the cancer cells forming the buds having phenotypic properties of cancer stem cells.…”
Section: Tumor Budding Invasion and Metastasismentioning
confidence: 98%
“…Cancer stem cells (CSC) are considered to be the main culprit of tumor local invasion and metastasis ( Marangon Junior et al, 2019 ). Tumor budding is known to be a morphological marker of tumor invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor budding is known to be a morphological marker of tumor invasion. Additionally, it has been suggested that tumor buds may have “stem cell” characteristics ( Marangon Junior et al, 2019 ). In our study, we found an association between tumor buds and CSCs.…”
Section: Introductionmentioning
confidence: 99%